Digital Fatigue and Urban Consumers’ Resistance Against E-Commerce Algorithms - Ahmad Abdul Rohman Aziz (PAPUA: International Journal of Sharia Business Management, 2025)
This study investigates the phenomenon of digital fatigue and its link to resistance behaviors among urban consumers navigating e-commerce platforms saturated with algorithmic personalization. This research applies a qualitative phenomenological approach to explore how individuals in Jakarta, Bandung, and Surabaya actively disengage from or manipulate recommendation systems in response to emotional and cognitive exhaustion. Data were collected from 25 participants through semi-structured interviews, revealing that 84% experienced mental fatigue due to algorithm-driven content repetition, intrusive notifications, and decision overload. The findings highlight various resistance strategies including browsing in incognito mode, clearing cookies, intentionally clicking unrelated content, and uninstalling apps acts rooted more in emotional autonomy than privacy concerns. Resistance behaviors were shown to vary by age and gender, with younger, tech-savvy users deploying technical measures and older participants favoring withdrawal methods. Additionally, over half of respondents expressed growing distrust in e-commerce platforms, citing manipulation and a lack of transparency as primary concerns. The study confirms that resistance is not passive avoidance but a form of digital agency where consumers renegotiate control over their online experiences. This work expands the discourse on algorithmic governance by showing that ethical engagement models must address emotional thresholds and user well-being, especially in non-Western urban environments. The implications are vital for developers, marketers, and policymakers aiming to balance personalization with sustainable digital interaction.